'Put the Statues in the Oven': Preliminary Results of Research on Steatite Sculpture from the Late Middle Kingdom*. Issue 1 (January 2015) - Connor, Simon; Tavier, Hugues; De Putter, Thierry
Identifying the material used to carve a statue is particularly significant. A sculpture might appear to be of a hard, prestigious stone, requiring a laborious process of manufacture, while actually be of a soft, more affordable stone. A large part of the corpus of sculptures of the Late Middle Kingdom and the Second Intermediate Period is made from a peculiar stone: steatite, also called soapstone or talc. Its specific characteristics allowed sculptors to produce pieces for the lower ranks of the elite. Soft and easily carved, steatite is transformed into a much harder material, enstatite (a mineral belonging to the pyroxene group) by firing. It also changes the soft and greyish appearance of steatite into a hard, dark or reddish stone. Steatite could thus be used to produce statues similar to those of higher officials (showing the same postures, gestures, clothes, headdresses, colour and apparent hardness), but using a much more affordable material. This process of transformation often makes steatite difficult to identify and it is frequently taken for basalt, greywacke or granodiorite, although basalt is rarely attested in statuary, and greywacke and granodiorite require slow, laborious carving. This article presents the corpus and gives keys to identify steatite statues, and describes the authors' experimentations to reconstruct the process of sculpting and firing steatite statuettes of the Egyptian lower elite.